2005
DOI: 10.1007/s10096-005-1357-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003

Abstract: Presented here is the 5-year impact of a national antimicrobial resistance surveillance system in Ireland, which was introduced in accordance with the European Antimicrobial Resistance Surveillance System (EARSS). Participation in EARSS began in Ireland in 1999. Initially, 12 laboratories serving a mix of general and tertiary hospitals participated, but by 2003, participation had increased to 28 laboratories with a population coverage of 89%. During 1999-2003, 4,146 episodes of Staphylococcus aureus bacteraemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Ireland has a serious problem with MRSA, and the proportion of MRSA among S. aureus blood culture isolates is among the highest in Europe (11). It has been reported that in areas where MRSA is endemic, the introduction of a full "searchand-destroy" approach, including screening of all patient contacts of all index cases and the institution of precautionary isolation for all such contacts, could reduce the prevalence of MRSA to Ͻ1% within 6 years (1).…”
Section: Discussionmentioning
confidence: 99%
“…Ireland has a serious problem with MRSA, and the proportion of MRSA among S. aureus blood culture isolates is among the highest in Europe (11). It has been reported that in areas where MRSA is endemic, the introduction of a full "searchand-destroy" approach, including screening of all patient contacts of all index cases and the institution of precautionary isolation for all such contacts, could reduce the prevalence of MRSA to Ͻ1% within 6 years (1).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA isolates investigated for the presence of pvl genes were recovered from patients in the following hospitals: any of the 28 Irish hospitals from geographically diverse areas that participated in the European Antimicrobial Resistance Surveillance System (EARSS) during 2003 and reported patients with MRSA-positive blood cultures (n ϭ 18) (this level of participation provided an estimated population coverage of 89%; the 28 hospitals consisted of 7 tertiary referral university teaching hospitals, 2 regional hospitals, 12 general hospitals, 2 private hospitals, 2 maternity hospitals, 2 pediatric hospitals, and 1 long-stay care hospital) (27,40); 1 maternity hospital (with 188 beds); 2 pediatric university teaching hospitals (1 with 236 and 1 with 150 beds); and 1 tertiary referral adult university teaching hospital (with 936 beds).…”
Section: Methodsmentioning
confidence: 99%
“…2007). These and other such systems have been able to document trends over time and also stimulate helpful action at local, national and regional level (Murphy et al. 2005; Bartoloni et al.…”
Section: Introductionmentioning
confidence: 99%